2007
DOI: 10.1057/palgrave.jcb.3050062
|View full text |Cite
|
Sign up to set email alerts
|

Investing in new medical technologies: A decision framework

Abstract: Purchasing and reimbursement decisions in healthcare systems with fi nite resources are increasingly infl uenced by formal health economic analysis. It is therefore sensible for a company considering the development of a new medical technology to assess its potential cost effectiveness as early as possible in the development cycle. This document describes a process by which an organisation can add rigour to decisions about which technologies to pursue, as well as creating a persuasive argument for outside inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Investors, unsurprisingly, were reported as not wanting to invest in a company that had uncertain product sales. It was suggested that one way in which companies might overcome this barrier was to perform economic modelling early on in the product development phase to establish what sort of clinical benefit would sustain a product marketed at a certain price [28]. Indeed, most of the companies that did not have products on the market at the point of the interview mentioned that they try to address reimbursement issues early on by keeping prices low.…”
Section: Reimbursement Processmentioning
confidence: 99%
“…Investors, unsurprisingly, were reported as not wanting to invest in a company that had uncertain product sales. It was suggested that one way in which companies might overcome this barrier was to perform economic modelling early on in the product development phase to establish what sort of clinical benefit would sustain a product marketed at a certain price [28]. Indeed, most of the companies that did not have products on the market at the point of the interview mentioned that they try to address reimbursement issues early on by keeping prices low.…”
Section: Reimbursement Processmentioning
confidence: 99%
“…The purpose of performing early HTA at this stage of the product development process is to assist health technology firms in making realistic commercial valuations of the conceived new products by providing for each potential new biomarker technology a rough estimate of the maximum additional cost for which its intended clinical application is still likely to be cost effective. In this section, we will describe how this upper bound on the technology's cost, also known as the commercial headroom available [13], can be estimated for an improved, biomarker-based screening test.…”
Section: Added Predictive Value and Cost-effectiveness Of Novel Biomamentioning
confidence: 99%
“…The aim of this approach is to improve the development decisions made and increase the likelihood of the product being commercially successful (Craven et al, 2009;Cosh et al 2007). We propose that this concept could also be applied to the assessment of the value of healthcare technology innovations developed by academia, for example at the early stages of either a research funding application or during technology transfer.…”
Section: Titlementioning
confidence: 99%
“…Stage 4 of the post-development testing stage in Figure 4. Within MATCH we have worked with industry to embed this type of assessment approach earlier in the development process (Craven et al, 2009;Cosh et al, 2007), e.g. Stage 2 of the pre-development investigation stage in Figure 4.…”
Section: Stage Gate Modelmentioning
confidence: 99%